Design of grid connected photovoltaic power plant: for Al-Ahliyya Amman University in Jordan - Haj Dawood, Ahmad Helmi Dawood (2022)
The Photovoltaic power plant is considered one of the most important renewable energy resources economically and environmentally. This project proposes the production and performance analysis for a GCPV power plant. The high irradiance and high tariff rate for the private sectors in Jordan are the main factors that encourage the usage of a renewable energy source to reduce the annual electricity bill. The tariff rate for Al-Ahliyya Amman University is 0.36 $/kWh and annual energy consumption is 4 GWh. The proposed power plant size is set to be 985 kWp on a 7,550 m2 available area designed using three methods which are mathematical equations, PVsyst software and Helioscope. Different methods are used to identify the power plant annual production and performance considering orientation, arrangement and irradiance losses. The mathematical equations annual production is 1616.041 MWh, performance ratio of 80%, payback period of 1 year and 11 months and CO2 emission of 24240.615 tCO₂. The PVsyst software method annual production is 1704.4 MWh, average performance ratio 83.4%, payback period of 2 years and CO2 emission of 24628.6 tCO₂. Lastly the Helioscope software annual production is 1,343.4 MWh, performance ratio of 80.8% and payback period of 2 years and 5 months CO2 emission of 19406.35 tCO₂. It‟s found that mathematical equations and PVsyst software obtained similar results of annual production and payback period comparing to the Helioscope due to the consideration of the location irradiance. For this study it‟s found that the PVsyst achieved the highest energy generation, annual electricity saving and CO2 emission due to the consideration of orientation, irradiance changes, detailed losses factors and sizing